2020
DOI: 10.2196/20488
|View full text |Cite
|
Sign up to set email alerts
|

Digital Cardiovascular Biomarker Responses to Transcutaneous Cervical Vagus Nerve Stimulation: State-Space Modeling, Prediction, and Simulation

Abstract: Background Transcutaneous cervical vagus nerve stimulation (tcVNS) is a promising alternative to implantable stimulation of the vagus nerve. With demonstrated potential in myriad applications, ranging from systemic inflammation reduction to traumatic stress attenuation, closed-loop tcVNS during periods of risk could improve treatment efficacy and reduce ineffective delivery. However, achieving this requires a deeper understanding of biomarker changes over time. Obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These findings suggest that tcVNS may target the underlying neurobiology of PTSD, in particular noradrenergic and peripheral sympathetic nervous system function. The findings are consistent with our prior studies showing a decrease in sympathetic nervous system activity when tcVNS is paired with traumatic reminders in traumatized individuals ( Gazi et al, 2020 ; Gurel et al, 2020a ; Gurel et al, 2020b ; Gurel et al, 2020e ), as well as numerous studies showing nVNS (taVNS) blocks peripheral sympathetic nervous system function and startle reflex ( Bretherton et al, 2019 ; Clancy et al, 2014 ; Lamb et al, 2017 ). Symptoms of hyperarousal reduced by tcVNS in this study include increased attention and vigilance, being on guard, poor concentration and sleep.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that tcVNS may target the underlying neurobiology of PTSD, in particular noradrenergic and peripheral sympathetic nervous system function. The findings are consistent with our prior studies showing a decrease in sympathetic nervous system activity when tcVNS is paired with traumatic reminders in traumatized individuals ( Gazi et al, 2020 ; Gurel et al, 2020a ; Gurel et al, 2020b ; Gurel et al, 2020e ), as well as numerous studies showing nVNS (taVNS) blocks peripheral sympathetic nervous system function and startle reflex ( Bretherton et al, 2019 ; Clancy et al, 2014 ; Lamb et al, 2017 ). Symptoms of hyperarousal reduced by tcVNS in this study include increased attention and vigilance, being on guard, poor concentration and sleep.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that tcVNS blocks IL-6 and IFNγ response to traumatic script stress in PTSD ( Bremner et al, 2020a ) and blocks the rise in Pituitary Adenylate Cyclase Activating Peptide (PACAP) over three days of stressful tasks in traumatized subjects with and without PTSD ( Gurel et al, 2020c ). We also previously reported that tcVNS in traumatized healthy human subjects with and without PTSD blocked peripheral sympathetic and enhanced parasympathetic responses both at baseline and in response to both personalized traumatic scripts and mental stressors ( Gazi et al, 2020 ; Gurel et al, 2020a ; Gurel et al, 2020b ; Gurel et al, 2018 ; Gurel et al, 2020d ; Gurel et al, 2020e ) and modulated brain response to traumatic scripts ( Wittbrodt et al, 2020 ), and other studies reported that tcVNS blocked sympathetic function in healthy subjects ( Brock et al, 2017 ; Lerman et al, 2019 ) while taVNS blocked sympathetic function in healthy human subjects ( Badran et al, 2018b ; Bretherton et al, 2019 ; Clancy et al, 2014 ) and patients with co-morbid mild Traumatic Brain Injury (mTBI) and PTSD ( Lamb et al, 2017 ). This work replicated findings in healthy subjects using implanted VNS ( Schomer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 76%
“…Future work may also include other tests, such as a cognitive aptitude assessment, social stress test or mental arithmetic (Bauerly et al, 2019 ; Duschek et al, 2009 ; Gurel et al, 2020a ; Tornatzky & Miczek, 1993 ), that can induce more central nervous system mediated responses and, therefore, increase the utility of EDA, pupil diameter, and other recorded modalities. Recent work has also shown that biomarkers, like HR and PPG amplitude, can be used to predict responses to transcutaneous cervical vagus nerve stimulation (tcVNS) and model dynamic characteristics of an adapting ANS (Gazi et al, 2020 ). While it is unclear how this may scale for other conditions or interventions, modeling biomarker responses can be applied to continuously monitoring vital-sensing devices to calculate real-time risk scores and further comprehensive index values related to autoimmune health.…”
Section: Discussionmentioning
confidence: 99%
“…Future work may also include other tests, such as a cognitive aptitude assessment, social stress test or mental arithmetic (Tornatzky & Miczek, 1993; Duschek et al, 2009; Bauerly et al, 2019; Gurel et al, 2020), that can induce more central nervous system mediated responses and, therefore, increase the utility of EDA, pupil diameter, and other recorded modalities. Recent work has also shown that biomarkers, like heart rate and PPG amplitude, can be used to predict responses to transcutaneous cervical vagus nerve stimulation (tcVNS) and model dynamic characteristics of an adapting ANS (Gazi et al, 2020). While it is unclear how this may scale for other conditions or interventions, modeling biomarker responses can be applied to continuously monitoring vital-sensing devices to calculate real-time risk scores and further comprehensive index values related to autoimmune health…”
Section: Discussionmentioning
confidence: 99%